Introduction: Journalism and algorithms - Lemos, André; Domingo, David (Brazilian journalism research, 2020)
Making sense of the mutual shaping of journalism and algorithms requires research that closely analyses developments in very concrete, precise settings, but also studies that take a wider, theoretical perspective, or that put this evolution in historical context. This special issue provides this variety of points of view to contribute to the understanding of the opportunities and the challenges at the intersection between journalism and technology today.